Assessment practices of speech-language pathologists for cognitive communication disorders following traumatic brain injury in adults: An international survey. (December 2014) - Frith, Matthew; Togher, Leanne; Ferguson, Alison; Levick, Wayne; Docking, Kimberley
Abstract Primary objective: This study's objective was to examine the current assessment practices of SLPs working with adults with acquired cognitive communication impairments following a TBI. Methods and procedures: Two hundred and sixty-five SLPs from the UK, the US, Canada, Australia and New Zealand responded to the online survey stating the areas of communication frequently assessed and the assessment tools they use. Main outcomes and results: SLPs reported that they routinely assessed functional communication (78.8%), whereas domains such as discourse were routinely assessed by less than half of the group (44.3%). Clinicians used aphasia and cognitive communication/high level language tools and tools assessing functional performance, discourse, pragmatic skills or informal assessments were used by less than 10% of the group. The country and setting of service delivery influenced choice of assessment tools used in clinical practice. Conclusions: These findings have implications for training of SLPs in a more diverse range of assessment tools for this clinical group. The findings raise questions regarding the statistical validity and reliability of assessments currently used in clinical practice. It highlights the need for further research into how SLPs can be supported in translating current evidence about the use of assessment tools into clinical practice.